Islamic Boarding School And The Hardiness Of Santri: Collaboration Of Islamic Religious Teachers And Guidance And Counseling At Pesantren - Karimah, Ummah; Ayuhan, Ayuhan; Yunus, Ahmad; Zulfikri, Alif (IAIN Kudus, 2023)
Islamic Boarding School And The Hardiness Of Santri: Collaboration Of Islamic Religious Teachers And Guidance And Counseling At Pesantren. This study aims to analyze and describe the form of implementation of the collaboration between PAI teachers and BK teachers in developing the hardiness of students at Darul Arqam Sawangan Islamic Boarding School. Hardiness is a personality that must be owned by students in carrying out life in Islamic boarding schools when facing the problems they face. The importance of doing this research because there are still minimal guidance and counseling services that are carried out and can be done in collaboration with PAI teachers in islamic boarding school. This research method used a qualitative method with a descriptive approach. The data collection techniques through three methods, including: interviews, documentation, observation, and field notes (documentation). The data analysis technique used the stages of data reduction, data presentation, and conclusions. The results of this study indicated that the form of implementation of the collaboration between PAI teachers and BK teachers in developing the hardiness of students by sharing their respective tasks, such as PAI teachers who provided material to become hardiness students during teaching and learning activities and provide information related to the progress of students. Whereas, BK teachers run the BK program through personal field services for students with classical guidance techniques and group counseling. This study has limitations due to the background of students is various, this does not rule out the possibility that the level of toughness of students is different and in providing material about hardiness and it cannot be expected that all students will experience an increase.Keywords: PAI Teachers; BK Teachers; Hardiness; Islamic Boarding Schools; Santri